"Irresponsible lending" with a better informed lender - Roman Inderst (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2009)
We present a simple model of personal finance in which an incumbent lender has an information advantage vis-a-vis both potential competitors and households. In order to extract more consumer surplus, a lender with sufficient market power may engage in irresponsiblelending, approving credit even if this is knowingly against a household's best interest. Unless rival lenders are equally well informed, competition may reduce welfare. This holds, in particular, if less informed rivals can free ride on the incumbent's superior screening ability.
urn:nbn:de:hebis:30-72920
Keywords: 330